2020
DOI: 10.1371/journal.pone.0230230
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting of self-renewal, migration and invasion of ovarian cancer stem cells by blocking TGF-β pathway

Abstract: Objective To investigate the effect and mechanism of SB525334 on self-renewal, migration and invasion of ovarian cancer stem cells. Methods ALDHhigh-expressing cancer stem cells (CSCs) were isolated from human ovarian cancer cell line SKOV-3 by flow cytometry and treated with 2μg/mL SB525334 for 6h. The sphere forming assay was used to detect the ability of self-renewal of CSCs and the colony formation assay was used to detect the tumorigenicity in vitro. Transwell migration and invasion assay were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The high expression of TGF-β3 is associated with poor prognosis of high-grade serous carcinoma, and it is a potential indicator for the evaluation of ovarian cancer prognosis (57). Recent studies have reported that in ovarian cancer stem cells, inhibition of TGF-β/SMAD pathway activation can further inhibit EMT (58)(59)(60). In 2012, Kulbe et al (61) first described the 'TNF' network in the ovarian cancer microenvironment.…”
Section: Cell Signaling and Exosome-mediated Tumor Immune Microenviromentioning
confidence: 99%
“…The high expression of TGF-β3 is associated with poor prognosis of high-grade serous carcinoma, and it is a potential indicator for the evaluation of ovarian cancer prognosis (57). Recent studies have reported that in ovarian cancer stem cells, inhibition of TGF-β/SMAD pathway activation can further inhibit EMT (58)(59)(60). In 2012, Kulbe et al (61) first described the 'TNF' network in the ovarian cancer microenvironment.…”
Section: Cell Signaling and Exosome-mediated Tumor Immune Microenviromentioning
confidence: 99%
“…Huang et al used a precision-cut liver tissue slice model that included all major cell types of liver parenchyma and showed anti-fibrotic effects of SB525334 in liver cells after bile duct ligation [27]. Other studies evaluated the influence of SB525334 on cancer models and revealed its inhibitory effects on the migration, invasion and EMT of cancer cells in the esophagus, liver, ovary and pancreas [8][9][10][11]. Furthermore, SB525334 attenuates the collagen production by reducing NADPH oxidase 4 in myoblasts [28].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the transcription of the TGF-β-target genes, such as Snail, is initiated, which, in turn, triggers EMT. SB525334 is a potent TβRI inhibitor; previous studies have demonstrated that SB525334 blocks TGF-β-induced Smad activation and decreases EMT in some tissues/cell lines [8][9][10][11]. Considering the association between TGF-β signaling and EMT in peritoneal mesothelial cells, SB525334 may attenuate TGF-β signaling, resulting in a decrease in EMT and peritoneal membrane fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the inhibitory effect on self-renewal [ 84 ], a single secondary CSC-enriched spheroid was isolated and treated with jorunnamycin A (0–0.5 µM). The alteration of spheroids after 0–7 days of jorunnamycin A treatment was observed under an inverted microscope (Nikon Ts2, Nikon, Japan) and presented as a relative value to spheroid size at day 0.…”
Section: Methodsmentioning
confidence: 99%